Introduction to technology commercialisation - Terziovski, Milé (Henry Stewart Talks, 2025)
Technology commercialisation and innovation capability, Overview of the commercialisation process, Benefits of successful commercialisation, Main challenges of the commercialisation process, Building innovation capability